Efek Penggunaan Strategi Konflik Kognitif terhadap Hasil Belajar Kognitif Siswa - Verawati, Ni Nyoman Sri Putu; Afifah, Gusti (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2018)
This study aims to determine the effect of using the conflict cognitive strategies on students' cognitive learning achievements. This research is an experimental study using one group pretest-posttest design. The research sample was 35 students of class X MIPA 7 at SMAN 2 Mataram. The conflict cognitive strategies are conditioned in research on the subject matter of Regular Straight Motion and Regular Changed Straight Motion. Measurement of cognitive learning outcomes using test instruments and given to students as pretest and posttest. The test instrument was previously validated by 2 (two) validators on the content and construct aspects. The validation results show that the test instrument has been declared valid on the content and construct aspects with a validity (Va) level of 4.12 and 4.00. The results showed that students' cognitive learning achievements improved after learning using the conflict cognitive strategies (mean of 3.49) significant (p <0.05). These results are also supported by the results of n-gain analysis of cognitive learning achievements of students after learning with a value of 0.74 with a high category so that it is declared effective to improve students' cognitive learning achievements.